The design and evaluation of an integrated training load and injury/illness surveillance system in competitive swimming. (March 2023) - Barry, Lorna; Lyons, Mark; McCreesh, Karen; Powell, Cormac; Comyns, Tom
Abstract: Objective: To design and evaluate an integrated training load monitoring and injury/illness surveillance system in a competitive swimming environment. Design: Descriptive/mixed methods. Setting: Swim Ireland National Training Centres. Participants: Fourteen competitive athletes and seven coaches/medical data collectors participated in the evaluation process. Outcome measures: System satisfaction, usefulness and burden were evaluated. Barriers to the implementation and effectiveness of the system were explored. Results: Most athletes were 'extremely' or 'very' satisfied with the overall data collection process and also found it to be 'extremely' or 'very' useful in the training centre environment. All practitioners were 'extremely satisfied with the system and found it to be either 'extremely' or 'very' useful in their role. Process constraints and data access and control were significant themes related to the athletes, while practitioners highlighted communication and cooperation amongst stakeholders, layering context to the data, maintaining data integrity and the coach's influence in the monitoring process as being important to the monitoring/surveillance process. Conclusions: Training load monitoring and injury/illness surveillance are necessary to elevate the standard of prospective injury/illness prevention research. Integrated systems should be designed in line with key consensus statements, while also being implemented in a way that counteracts the challenges within the real-world training environment. Highlights: An integrated monitoring system should meet research best practice standards. Methodological processes should also consider stakeholder adherence/engagement. Integrating training load and injury/illness surveillance optimises context and understanding. Coaches' beliefs have a large influence on the monitoring process. Integrated monitoring was fundamental to global communication among stakeholders.